2017
DOI: 10.3748/wjg.v23.i16.2940
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effects of nesfatin-1 on gastric function in obese rats

Abstract: AIMTo investigate the effects of nesfatin-1 on gastric function in obese rats.METHODSThe obese rat model was induced by a high-fat diet. The gastric emptying rate and gastric acid secretory capacity of the rats were determined after treatment with different drug concentrations of nesfatin-1 and administration routes. Based on this, the expression of H+/K+-ATPase was measured using RT-PCR and western blot to preliminarily explore the mechanism of gastric acid secretion changes.RESULTSBody weight, body length, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Central (4 th -ventricular) administration of nesfatin-1 increases c-Fos expression in the rat DMV and induces a dose-dependent increase in calcium influx in the overwhelming majority of cultured DMV neurons, suggesting a direct regulatory action on vagal outflow (96). Indeed, central (icv) administration of nesfatin-1 inhibited the antroduodenal motility of mice in a dose-dependent fashion (2) and reduced gastric emptying of rats (88,100). In addition to its actions to modulate gastric motor functions, nesfatin-1 has also been shown to inhibit secretory functions, including both basal and vagally stimulated (2-deoxy-D-glucose-induced) gastric acid production (96,100).…”
Section: Nesfatin-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Central (4 th -ventricular) administration of nesfatin-1 increases c-Fos expression in the rat DMV and induces a dose-dependent increase in calcium influx in the overwhelming majority of cultured DMV neurons, suggesting a direct regulatory action on vagal outflow (96). Indeed, central (icv) administration of nesfatin-1 inhibited the antroduodenal motility of mice in a dose-dependent fashion (2) and reduced gastric emptying of rats (88,100). In addition to its actions to modulate gastric motor functions, nesfatin-1 has also been shown to inhibit secretory functions, including both basal and vagally stimulated (2-deoxy-D-glucose-induced) gastric acid production (96,100).…”
Section: Nesfatin-1mentioning
confidence: 99%
“…Indeed, central (icv) administration of nesfatin-1 inhibited the antroduodenal motility of mice in a dose-dependent fashion (2) and reduced gastric emptying of rats (88,100). In addition to its actions to modulate gastric motor functions, nesfatin-1 has also been shown to inhibit secretory functions, including both basal and vagally stimulated (2-deoxy-D-glucose-induced) gastric acid production (96,100).…”
Section: Nesfatin-1mentioning
confidence: 99%
“…Obesity is a global public health priority. With the improvement of people's standard of living, the number of obese Chinese has grown to an annual rate of 38.1% over the past several years [1]. Obesity is currently one of the major health concerns in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…While ghrelin seems to be an important modulator of gastrointestinal functions in mammals, whether this function is conserved in fish is poorly understood . Some studies have demonstrated that ghrelin contributes to gastric emptying and gastric acid secretory capacity in rats (Tian et al, 2014;Yang et al, 2017). To date, no data is available on gastric functions of nesfatin-1 in fish.…”
mentioning
confidence: 99%